Optimization of Temperature, pH and Duration for Enhanced Antibiotic Productivity of Microbes Isolated from Sea Cucumber - Sudhan, S. Hari Hara (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Five sea cucumber species were collected from fishermen at coastal region of Kanyakumari district, Tamil Nadu, and dissected aseptically. Intestinal fluids and coelomic fluids were collected. After serial dilution of the collected fluids, primary screening was carried out by crowded plate method using modified Soybean Casein Agar media (Kester et al.). Selected antibiotic-producing organisms producing zone of inhibition (ZOI) higher than 6 mm (ZOI >6 mm) were evaluated for broad spectrum of activity using two Gram positive, two Gram negative, and two fungal species by perpendicular streak method. Biochemical characterization and nutrient optimization were carried out for selected three isolates (named IF32, IF52, and CF42) which were found to have broad spectrum of activity as well as passed Kirby–Bauer antimicrobial susceptibility test. This article focuses on optimization of temperature, pH, and duration for maximum antibiotic productivity of the selected isolates. Methodology: Optimum temperature, pH, and duration of maximum antibiotic production were evaluated for the selected antibiotic producers. Crude antibiotic was collected after 24 h of incubation under different temperature and pH conditions and tested against Staphylococcus aureus (MTCC 1430). The specific temperature and pH at which maximum ZOI was produced by the collected crude extracts against test organisms were considered. The duration of maximum antibiotic production was evaluated by incubating the isolated organisms under the optimized temperature and pH. Results: The optimum temperature for the production of crude antibiotic from IF32, IF52, and CF42 was found to be 32°C, 35°C, and 31°C, respectively. The pH at which maximum antibiotic production was observed is found to be 8, 7, and 9, respectively, for IF32, IF52, and CF42. The duration of maximum antibiotic productivity at the optimized conditions was found to be 4th, 5th, and 3rd days, respectively, for IF32, IF52, and CF42.